Whole Genome Sequence Analysis of Porcine Astroviruses Reveals Novel Genetically Diverse Strains Circulating in East African Smallholder Pig Farms - Amimo, Joshua O.; Machuka, Eunice M.; Okoth, Edward A.; Vlasova, Anastasia N.; Pellé, Roger (MDPI, 2020)
Astroviruses (AstVs) are widely distributed and are associated with gastroenteritis in human and animals. The knowledge of the genetic diversity and epidemiology of AstVs in Africa is limited. This study aimed to characterize astroviruses in asymptomatic smallholder piglets in Kenya and Uganda. Twenty-four samples were randomly selected from a total of 446 piglets aged below 6 months that were initially collected for rotavirus study and sequenced for whole genome analysis. Thirteen (13/24) samples had contigs with high identity to genus Mamastrovirus. Analysis of seven strains with complete (or near complete) AstV genome revealed variable nucleotide and amino acid sequence identities with known porcine astrovirus (PoAstV) strains. The U083 and K321 strains had nucleotide sequence identities ranging from 66.4 to 75.4% with the known PoAstV2 strains; U460 strain had nucleotide sequence identities of 57.0 to 65.1% regarding the known PoAstV3; and K062, K366, K451, and K456 strains had nucleotide sequence identities of 63.5 to 80% with the known PoAstV4 strains. The low sequence identities (<90%) indicate that novel genotypes of PoAstVs are circulating in the study area. Recombination analysis using whole genomes revealed evidence of multiple recombination events in PoAstV4, suggesting that recombination might have contributed to the observed genetic diversity. Linear antigen epitope prediction and a comparative analysis of capsid protein of our field strains identified potential candidate epitopes that could help in the design of immuno-diagnostic tools and a subunit vaccine. These findings provide new insights into the molecular epidemiology of porcine astroviruses in East Africa.